Plastic Design of a Pressure Vessel - Li, Cheng; Bing-Ye, Xu; Kenchin, Hwang (Engineering Transactions, 1987)
The limit loads are given for various collapse mechanisms of a pressure vessel consisting of a cylindrical shell and hemispherical drumheads. Boundaries of different collapse mechanisms are determined in a parameter space compassing the applicable range of vessel geometries. Limit loads corresponding to the neighboring collapse mechanisms remain continuous across these boundaries. These results shed some light on the plastic design and failure assessment in pressure vessel technology.